DNA stool test for colorectal cancer: hypermethylation of the secreted frizzled-related protein-1 gene. - Zhang, Wei; Bauer, Michael; Croner, Roland S.; Pelz, Jörg Otto Wilhelm; Lodygin, Dimitri; Hermeking, Heiko; Stürzl, Michael; Hohenberger, Werner; Matzel, Klaus (Diseases of the colon & rectum, 2007)
To investigate a potential mode of noninvasive screening for colorectal cancer, we evaluated the hypermethylation of the secreted frizzled-related protein-1 gene promoter in human stool DNA. In stool samples from 36 patients with colorectal neoplasia (7 adenoma, 29 colorectal cancer) and 17 healthy control subjects, isolated DNA was treated with sodium bisulfite and analyzed by methylation-specific polymerase chain reaction with primers specific for methylated or unmethylated promoter sequences of the secreted frizzled-related protein-1 gene. Hypermethylation of the secreted frizzled-related protein-1 promoter was present in the stool DNA of patients with adenoma and colorectal cancer. A sensitivity of 89 percent and specificity of 86 percent were achieved in the detection of colorectal neoplasia. The difference in hypermethylation status of the secreted frizzled-related protein-1 promoter between the patients with colorectal neoplasia and the control group was statistically highly significant (P < 0.001). Adenoma and early tumor Stage I (International Union Against Cancer) displayed both unmethylated and methylated secreted frizzled-related protein-1 promoter sequences, whereas advanced tumor stages showed only methylated secreted frizzled-related protein-1 (P = 0.05). The results indicate that this DNA stool test of hypermethylation of the secreted frizzled-related protein-1 promoter is a sensitive and specific method. It has the potential of a clinically useful test for the early detection of colorectal cancer. PURPOSE METHODS RESULTS CONCLUSIONS
Keywords: DNA methylation; Colorectal cancer; Secreted frizzled-related protein; Stool DNA test; Epigenetic marker; Cancer screening